The relation between life quality and subtype of the disease in patients with irritable bowel syndrome - Kayar, Yusuf; Agin, Mehmet; Unver, Nurcan; Dertli, Ramazan; Kirpinar, Ismet (Annals of Medical Research, 2021)
None
Keywords: None